Appreciative enquiry peer review improving quality of services. Issue 5 (10th June 2019) - Burbach, Frank R.; Amani, Sarah K.
Abstract : Purpose: Mental health service improvement initiatives often involve the setting of targets and monitoring of performance. The purpose of this paper is to describe the application of appreciative enquiry (AE), a radically different but complementary approach to quality assurance and improvement, to specialist mental health services across a health region. Design/methodology/approach: This case study describes a regional quality improvement (QI) project involving 12 early intervention in psychosis (EIP) services in South West England. In total, 40 people were trained in AE interviewing skills and in non-reciprocal peer review visits 59 interviews were conducted involving 103 interviewees including service users, carers, clinicians, managers and commissioners. Immediate verbal feedback was provided and main themes summarised in individual reports to host teams using the following headings: team values, strengths, dreams and development plans. A thematic analysis was conducted on team reports and a project report produced which summarised the stages and results of this regional initiative. Findings: All participants rated the experience as positive; it enhanced staff motivation and led to service development and improvement. Research limitations/implications: The experiences of these 12 EIP teams may not necessarily be generalisable to other services/regions but this positive approach to service improvement could be widely applied. Practical implications: AE is applicable in large-scale QI initiatives. Originality/value: To the authors knowledge this is the first time that AE has been applied to large-scale mental health service improvement and innovation.